Game Petualangan Belajar Bahasa Inggris Buah-Buahan Untuk Anak-Anak Dengan Teknologi Augmented Reality - Nasution, Muhammad Nawawi; Khair, Ummul; Annisah, Yessi Fitri (Universitas Harapan Medan, 2023)
Information technology was developed by humans in prehistoric times and functions as a system for recognizing the forms they are familiar with. They describe the information they get on cave walls, about hunting and the animals they hunt. Until now, information technology continues to develop, but its delivery and form are more modern. Technology can be interpreted as all processes carried out in an effort to realize something rationally. In this case, what is meant by something can be an application, machine, data or game. One way that can be done to integrate learning with technology that is interesting, fun, flexible and easier for students to accept is by using games in the learning process.